PENGARUH STRES KERJA, KEPUASAN KERJA DAN LOYALITAS KERJA TERHADAP KINERJA KARYAWAN PT. SAMUDERA GEMILANG DENPASAR - I Nyoman Resa Adhika; I Gede Rihayana; Putu Pradiva Putra Salain (Universitas Mahendradatta Denpasar, 2021)
This study was conducted to analyze and determine the effect of job stress, job satisfaction and employee loyalty on employee performance at PT. Samudera Gemilang Denpasar. This research method uses quantitative and qualitative methods by using primary and secondary data sources. The population in this study were all employees of PT. Samudera Gemilang Denpasar as many as 110 people. While the sample of respondents in this study were 86 people from all employees at Samudera Gemilang Denpasar. The result of the research is that work stress has a negative and significant effect on employee performance at Samudera Gemilang Denpasar, while job satisfaction and job loyalty have a positive and significant effect on employee performance at Samudera Gemilang Denpasar.